Comparison of bone mineral density between athletic and non-athletic Chinese male adolescents - Tsai, S. C.; Kao, C. H.; Wang, S. J. (Kaohsiung Journal of Medicine and Science, 1996)
For the evaluation of the effect of exercise on bone mineral density of adolescent athletes, twenty-nine Chinese male adolescent athletes, each of whom had regular training in his major sport which included baseball, swimming, judo and middle/long-distance running for one to six years and eight age-matched non-athletic controls were included in this study. Bone mineral density (BMD) was measured in all study subjects using dual photo absorptiometry at the second to fourth lumbar spines (L2-4) and the right femoral neck (FN). The results revealed the following: (1) the combined group of athletes had significantly greater BMD of L2-4 (1.08 +/- 0.09 g/cm2) than the control group (0.99 +/- 0.08 g/cm2) and a tendency for greater BMD of FN (1.15 +/- 0.13 g/cm2) than the control group (1.09 +/- 0.13 g/cm2); (2) judo majors had significantly greater BMD of L2-4 than baseball majors (P < 0.05), swimming majors (P < 0.01), track majors (P < 0.05) and controls (P < 0.005); (3) baseball majors had significantly greater BMD of L2-4 than controls (P < 0.05) and greater BMD of FN than swimming majors (P < 0.05), judo majors (P < 0.05), track majors (P < 0.005) and controls (P < 0.005); (4) body weight and body mass index (BMI) had good correlation with BMD of L2-4 and FN in control group, (5) in the combined group of athletes, weight and BMI were only strongly linked to BMD of FN, and not to BMD of L2-4. There was no good correlation between BMI and BMD of L2-4 and FN in any group of athletes. We concluded that (1) physical activity during adolescence may contribute significantly towards increasing BMD of athletes and (2) the training type may provide a specific stimulus for increasing BMD at specific localized sites experienced in training.